2017
DOI: 10.1016/j.pvr.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of human papillomavirus in lung cancer

Abstract: Lung cancer is the leading cancer worldwide among men and women with morbidity reaching 1.6 million. Human Papillomavirus is the causal factor of cervical cancer while its association with others is still under investigation. The purpose of our study is to examine the presence of HPV DNA as well as high-risk E6/E7 mRNA in patients with lung cancer.Lung tissues were collected during bronchoscopy and tested for HPV DNA and E6/E7 mRNA.67 lung tissue samples were analysed. The age range was 49–85 years old (y.o) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…In addition, some recent publications have indicated a positive link between HPV and etiopathogenesis of lung carcinoma, supporting the present findings (26,27). However, others have failed to identify such a causative link (28).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, some recent publications have indicated a positive link between HPV and etiopathogenesis of lung carcinoma, supporting the present findings (26,27). However, others have failed to identify such a causative link (28).…”
Section: Discussionsupporting
confidence: 89%
“…Chang et al [37], in addition to the evaluating the presence of HPV DNA, also evaluated the expression of p16 on NSCLC by IHC, and as a result, no correlation between the HPV and p16 expression was determined. Other authors, such as van Boerdonk et al [42], Bishop et al [43] and Doxtader et al [41], presented similar results, with 20 to 30% of NSCLC, both adenocarcinoma and squamous cell carcinoma, positive for p16 and negative for HPV DNA. In addition, these authors concluded Stage I -II 0 (0,0) 6 (10,5) 0,580 III -IV 10 (100,0) 51 (89,5) Total 10 (100) 60 (100) (*) Cases with missing values were excluded from the analysis n number; TNM staging: a system based on the size and/ or the extension of the primary tumor (T), the number of compromised lymph nodes (N) and the presence of metastasis (M).…”
Section: Discussionmentioning
confidence: 60%
“…Our results indicate that the stringent contamination precautions we took while conducting pre-PCR and PCR activities were sufficient for avoiding contamination. Moreover, the presence of HPV DNA does not signify an active HPV infection, and samples found positive for HPV DNA are frequently negative for HPV transcripts 14,25 . The measurement of viral E6/ E7 transcripts is widely considered the gold standard for detecting biologically-relevant HPV infection.…”
Section: Discussionmentioning
confidence: 99%